STYLISTIC DEVICES IN ENGLISH JOURNALISTIC TEXTS: STYLE, EXPRESSIVENESS, AND AUDIENCE STRATEGIES - Husanova Shahlo Zarifjon qizi (Western European Studies, 2026)
This article examines key stylistic and discursive features of English journalistic texts with particular emphasis on the interaction between analytical and commentative modes of writing. The study focuses on how factual analysis is combined with evaluative interpretation to influence readers’ understanding of social and political issues. Special attention is given to publicistic expressiveness, including metaphorical language and quotations, as essential tools for persuasion and credibility building in journalistic discourse. The article also considers audience-oriented language strategies, showing how journalists adapt lexical choice, tone, and rhetorical structure to meet the expectations of a target readership. By integrating these stylistic elements within a single analytical framework, the study demonstrates that effective journalistic texts rely not on isolated devices, but on the coherent interaction of analysis, evaluation, expressiveness, and reader engagement. The findings highlight the functional role of stylistic choices in shaping meaning and guiding reader interpretation in contemporary English journalism.
Keywords: journalistic discourse; analytical style; commentative style